PENGARUH PERSISTENSI LABA, BETA, DAN CORPORATE SOCIAL RE-SPONSIBILITY DISCLOSURE TERHADAP EARNINGS RESPONSE COEF-FICIENT PADA PERUSAHAAN JASA DI BURSA EFEK INDONESIA - Wardaya, Riyanto Adiguna; Lindrawati, Lindrawati (Jurnal Akuntansi Kontemporer, 2017)
Every company in developing a business has two alternatives, namely funding from creditors and investors. Investors need information about the company in making investment decisions. Information is the most profit responded by investors be-cause it provides an overview of the performance of the company, to measure the level of income, can use the Earnings Response Coefficient(ERC), a strong market response to earnings information is reflected in the high ERC. The purpose of this study was to examine and analyze the persistence of earnings, beta, and corporate social responsibility disclosure of the ERC. The study design was quantitative with the hypothesis. The data in the form of quantitative and qualitative research in the form of an annual report period 2012-2013, the stock price data and Composite Stock Price Index (CSPI) period of 2 days, 1 day prior to the announcement of the annual report, one day the announcement of the annual report. The object of research is a service company that is listed on the Indonesia Stock Exchange 2012-2013 period. Data were analyzed using multiple linear regression analysis. The analysis showed that the earnings persistence significant positive effect on the ERC, beta significant negative effect on the ERC and corpo-rate social responsibility disclosure no significant effect on the ERC. This suggests that investors may still provide a greater re-sponse to earnings information than social responsibility report in making investment decisions that are not found significant influence.